BAYI BERAT BADAN LAHIR RENDAH (BBLR) DAN KEMATIAN PERINATAL DI RUANG PERINATOLOGI RSUD dr . M. YUNUS BENGKULU - Buyung Keraman; Kheniva Diah Anggita (Jurnal Sains Kesehatan, 2017)
Perinatal death is the birth of life is the perfect outcome of conception from the mother who has been separated has signs of his life regardless of age of pregnancy. This study aims to study the relationship of low birth weight babies (BBLR) with perinatal mortality in the Perinatology Room RSUD. dr. M. Yunus Bengkulu. This research use cross sectional design. Population in this research all newborn in perinatology room of RSUD dr. M. Yunus Bengkulu in January-December 2016 as many as 653 people consisting of 293 people with LBW and 360 people not BBLR. Proportional sampling random sampling technique so that the number of samples will be taken as many as 87 people who consist of 39 babies babies with LBW and 48 babies who are not LBW. The data collection in this study used secondary data by looking at documentary documentation in the Perinatology Room of RSUD. dr. M. Yunus Bengkulu. Data analysis technique done by univariate and bivariat analysis with Chi-Square statistical test (c²) through SPSS program. The results of the study were : there were 52 (59.8%) infants who did not experience perinatal death, 48 (55.2%) of babies born not BBLR, there was a significant correlation between low birth weight infant with perinatal mortality in room perinatologi RSUD. dr. M. Yunus Bengkulu with moderate category, and low birth weight babies  were at risk 5 times perinatal mortality when compared with infants who are not low birth weight (LBW). It was expected that midwives could provide counseling to pregnant women to routinely check pregnancy, so that later could reduce complications arising from pregnancy in mothers who were at high risk.Keywords : baby, low birth weight, perinatal death